Interpersonal Emotion Regulation: Consequences for Brands in Customer Service Interactions - Reeck, Crystal; Onuklu, N. Nur Yazgan (Frontiers in Psychology, 2022)
This research demonstrates that interpersonal emotion regulation—attempts to manage others’ feelings—influences consumer perceptions during sales and service interactions impacting brand trust and loyalty. Building on previous research linking interpersonal emotion regulation to improved outcomes between people, across five experiments, we demonstrate that antecedent-focused interpersonal emotion regulation strategies result in enhanced brand loyalty and brand trust compared to response-focused interpersonal emotion regulation strategies. Analysis of mediation models reveals this effect is explained by changes in the consumer’s emotions, which in turn influence evaluations of the service interaction and subsequently impacts brand outcomes. We identify reactance as a moderator of this effect, such that customers with low (high) reactance to interpersonal regulation attempts exhibit more (less) favorable brand trust and loyalty evaluations. Further, we demonstrate that the visibility of interpersonal emotion regulation represents an important boundary condition. These findings support the process model of interpersonal emotion regulation and generate important insights for both theory and practice.